If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10(s + 2) = -42 Reorder the terms: -10(2 + s) = -42 (2 * -10 + s * -10) = -42 (-20 + -10s) = -42 Solving -20 + -10s = -42 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '20' to each side of the equation. -20 + 20 + -10s = -42 + 20 Combine like terms: -20 + 20 = 0 0 + -10s = -42 + 20 -10s = -42 + 20 Combine like terms: -42 + 20 = -22 -10s = -22 Divide each side by '-10'. s = 2.2 Simplifying s = 2.2
| 3a-2b=5a+6 | | 3(2l+3)=21 | | 8(x-10)-12=25x-143 | | 4(a-8)=16 | | (q-8)*5=30 | | a*6+1=9 | | 2(-x)=-1/4 | | 8x^7*x^8= | | 12=(.5)((x)(x))(.7) | | 4x^5=40 | | 6x-(-3x+10)=14 | | (V-4)2= | | 1=6tan(6x+7)-2 | | 9=11sin(9x) | | 3x^2+17-4x+3x^2+9x+5x= | | 2x+y=4x-2 | | 2n-3=37 | | 3x+23=55 | | 6-6(x+8)=-4x-(x-2) | | 6-6(x-8)=-4-(x-2) | | 4(2)X=128 | | 4-6g=24 | | 2m-6=-6-3-m | | -6(x+8)=-4-(x-2) | | 4x-168=4x-6 | | 3x+12=24x*(2+x) | | F(-5)=2(-5)+15 | | F(-5)=2-5+15 | | 10x^3-6x^2-12x-8=0 | | F(-5)=2x+15 | | 5m+11m+8+7m+2+2m=360 | | 4z-1-2z=3+3z |